Re-Creation Of Malaysian Traditional Game Namely ‘Baling Selipar’: A Critical Review - Addy Putra, Md Zulkifli; Amirul Fahmi, Razali; Nor Ziratul Aqma, Norzaman (2014)
Malaysian traditional game was a popular culture once, before the existence of foreign sports and virtual games. Nowadays, the activities of playing traditional games are getting lesser and there are insufficient efforts in preserving or recreating the game. Furthermore, the preference of today's teenagers towards computer games and foreign recreational activities endangered the existence of traditional game. It also opens themselves to health problems due to lack of physical activities. This research provides an attempt to re-create a traditional game so that the value of the traditional game can be preserved and suit today's trend. Several methods such as observation, field experiment and reference were used in the study. Quantitative method was used to get the final concept of the product. Although the research is not very extensive, the findings suggest that the traditional games are possible to be re-created as the new sport. Throughout the research, the specified game was re-created by focusing on the design of the rules, guidelines and equipment. Nevertheless, this is the preliminary conceptual game based on Baling Selipar, which will open a new dimension of recreating traditional games thus preserving the traditional games. In a nutshell, the new developed Baling Selipar game would be another alternative sport that is capable to be introduced to the society.